Arcadia - Lucas, Terry (2018)
This collaborative project contrives the possibility of a fictional future of academia in the skies. Each island represents different cultures, charms, and ways of thinking. Inspired by the steampunk culture and the game, BioShock Infinite, we envisage the juxtaposition of the mechanical flair of steampunk and fantasies of structures floating in the skies waiting to be explored.